Integrasi Kurikulum Internasional Dalam Peningkatan Mutu Pendidikan : Tinjauan Literatur Komparatif Antara Sekolah Negeri Dan Swasta Di Aceh: Integrasi Kurikulum Internasional Dalam Peningkatan Mutu Pendidikan : Tinjauan Literatur Komparatif Antara Sekolah Negeri Dan Swasta Di Aceh - Latifur Rahmi; Leny Nurdiyaningsih; Jamaluddin Idris (Jurnal Pustaka Cendekia Pendidikan, 2026)
The globalization of education has intensified demands for quality and competitiveness within education systems, particularly in producing graduates equipped with 21st-century competencies. In this context, the integration of international curricula such as Cambridge and the International Baccalaureate (IB) has emerged as an innovative strategy to enhance the quality of teaching and learning. This study aims to analyze differences in the implementation of international curriculum integration between public and private schools in Aceh, as well as its impact on educational quality. This research employs a systematic literature review method, examining scholarly publications from 2020 to 2026, using content analysis and thematic synthesis approaches. The findings reveal significant differences between public and private schools in terms of institutional readiness, implementation processes, and educational quality outcomes. Private schools tend to demonstrate greater effectiveness in integrating international curricula, supported by managerial flexibility, adequate resources, and access to professional development and global networks. In contrast, public schools continue to face several challenges, including limited teacher competencies, inadequate infrastructure, and regulatory frameworks that are not yet fully adaptive. These findings indicate that the successful integration of international curricula is strongly influenced by the overall readiness of the education system. Therefore, comprehensive policy support, capacity building of human resources, and strengthening of the educational ecosystem in public schools are essential to enable the optimal adoption of global educational practices.